Possible allusions to ancient Near Eastern solar mythology in Qohelet - a comprehensive enquiry - Prinsloo, G.T.M. (Gert Thomas Marthinus) (University of Pretoria, 2013)
Thesis (DLitt (Semitic Languages))--University of Pretoria, 2006.